2019
DOI: 10.1108/er-03-2018-0074
|View full text |Cite
|
Sign up to set email alerts
|

Specific HR practices and employee commitment: the mediating role of job satisfaction

Abstract: Purpose The purpose of this paper is to increase understanding of the influence mechanisms of specific HR practices variables – salary, job stability and job enrichment – upon employee commitment, through the mediating role of job satisfaction, in a developing country context. Crucially, these indicate employee commitment. Design/methodology/approach The study analyzed three specific HR practices with a sample of 263 employees in the banking industry of Pakistan. A structural equation modeling methodology is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
90
3
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(119 citation statements)
references
References 70 publications
15
90
3
11
Order By: Relevance
“…In line with our study's findings, the impact of HPWS on employee job satisfaction (Heffernan & Dundon, 2016;Kloutsiniotis & Mihail, 2017;Mahmood et al, 2019) as well as the impact of job satisfaction on organizational performance (Budie et al, 2019;Delaney & Huselid, 1996;Schyns & Croon, 2006) has been confirmed in several studies.…”
Section: Discussion and Comparisonsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with our study's findings, the impact of HPWS on employee job satisfaction (Heffernan & Dundon, 2016;Kloutsiniotis & Mihail, 2017;Mahmood et al, 2019) as well as the impact of job satisfaction on organizational performance (Budie et al, 2019;Delaney & Huselid, 1996;Schyns & Croon, 2006) has been confirmed in several studies.…”
Section: Discussion and Comparisonsupporting
confidence: 91%
“…According to the results of this study, when employee resilience, which is a set of individual skills and characteristics, is improved, this can have benefits both at the individual and organizational levels due the effective application of HPWS. In another study that looked at the banking industry, Mahmood et al (2019) confirmed that HPWS has a positive effect on organizational commitment of employees by enhancing their levels of job satisfaction.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Sementara itu, komitmen dianggap sebagai suatu keterikatan secara afektif dan emosional terhadap organisasinya sehingga individu berkomitmen terlibat dan menikmati keanggotaannya (Melewar et al, 2016;Miao & Cao, 2019). Di sisi lain, Chang & Chen (2011); Mahmood et al (2019) menjelaskan bahwa komitmen organisasi bisa dibentuk dari tindakan berupa finansial dan nonfinansial sehingga karyawan berusaha untuk memberikan yang terbaik kepada organisasinya.…”
Section: Komitmen Organisasiunclassified
“…Job satisfaction is one of the central areas of social research (Abdelmoteleb, 2019;Ashraf, 2019;Dhamija et al, 2019;Erro-Garces & Ferreira, 2019;Garcia et al, 2019;Magnier-Watanabeet al, 2019;Mahmood et al, 2019;Reçica & Doğan, 2019;Wu et al, 2019;Stater & Stater, 2009). At the root of this interest lies the premise that the phenomenon of job satisfaction can help explain the essence and dynamics of the potential of individuals and groups working in organizations, and thereby provide, among other things, valuable guidance for people management practices with a view to supporting more effective functioning of an individual within the organization, and potentially contributing to a better understanding of the individual's wellbeing bordering his or her professional and personal life (Chrupała-Pniak, 2012, pp.…”
Section: Introductionmentioning
confidence: 99%